The Role of Teaching Factory in Shaping Professional Character of Marketing Students at SMKN 6 Surakarta - Rasela Febriana; Surya Jatmika (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2025)
Vocational High Schools (SMK) aim to produce graduates who not only possess technical skills but also demonstrate professional character in accordance with industry needs. However, the gap between students’ competencies and labor market demands remains significant, as reflected in the unemployment rate of SMK graduates, which reached 9.1% (BPS, 2025). This study aims to analyze the role of the Teaching Factory (TeFa) in shaping students’ professional character in the Marketing expertise program at SMKN 6 Surakarta, particularly through the Viska Mart retail business practice unit. This research employed a qualitative approach with a case study design. Data were collected through semi-structured interviews, observations, and documentation, and analyzed using the interactive model of Miles, Huberman, and Saldaña. The findings indicate that the implementation of TeFa effectively fosters values of responsibility, discipline, honesty, accuracy, communication, and teamwork through operational practice experiences, cashier management, inventory control, customer service, and product marketing. Nevertheless, several challenges remain, including informal character evaluation, limited industrial monitoring, and students’ inconsistent attitudes and motivation. This study concludes that TeFa implementation contributes significantly to the development of students’ professional character, with promising prospects for strengthening systematic character evaluation and enhancing industry involvement to broaden real-world practice experiences.